Biomarker-guided implementation of the old drug temozolomide as a novel treatment option for patients with metastatic colorectal cancer. (January 2020) - Pietrantonio, Filippo; Randon, Giovanni; Romagnoli, Dario; Di Donato, Samantha; Benelli, Matteo; de Braud, Filippo
Highlights: MGMT promoter methylation is observed in up to 40% of colorectal tumors. Activity of temozolomide in MGMT methylated metastatic colorectal cancer is low. Novel biomarkers are being developed including MGMT quantitative methylation and protein expression. Temozolomide in combination with synergic drugs proved to be highly active without significant toxicity. Temozolomide resistant tumors due to inactivation of mismatch-repair key genes are sensitized to immunotherapy. Abstract: Temozolomide is an oral alkylating agent used for treating several cancers including glioblastoma and melanoma. Promising, albeit limited, activity and efficacy of temozolomide have been reported in pretreated patients with metastatic colorectal cancer bearing MGMT promoter methylation. MGMT silencing and proficiency of the mismatch repair system were considered the major predictive biomarkers of sensitivity to temozolomide. Refinement of established biomarkers and integration with those related to alteration in specific DNA-damage response pathways such as base excision repair are promising strategies for selecting metastatic colorectal patients to this old drug with several potential novel applications. Then, mounting preclinical and clinical observations have linked acquired resistance to temozolomide to emergence of alterations in the mismatch repair system. Whilst accounting for tumor cells capability of escaping apoptosis when exposed to temozolomide, inactivation of key mismatch-repair proteins will ultimately lead to increasing tumor mutational burden. This drug-induced mismatch deficient-like phenotype is being exploited in proof-of-concept trials combining temozolomide and immune checkpoint inhibitors in metastatic colorectal cancer.